Bullion Bank Regulation in Indonesia in an Effort to Protect Customers - Sofyan Sauri; Handar Subhandi Bakhtiar; Atik Winanti (Lead Journal of Economy and Administration, 2025)
The development of the global financial system has encouraged various countries to adopt bullion banks as an alternative to the gold-based financial system. However, in Indonesia, the concept of bullion banks is still relatively new and does not yet have a clear legal framework. This study aims to examine the need for bullion bank regulation in Indonesia and to assess the suitability of the national legal framework with international practices. The method used is normative juridical with a statutory approach and comparative studies. The results of the study show that Indonesia does not yet have specific regulations regarding bullion banks, which has the potential to cause legal uncertainty for business actors and investors. Therefore, it is necessary to formulate comprehensive regulations to regulate bullion bank activities specifically to support the stability of the national financial system. This study recommends that policy makers immediately formulate regulations related to bullion banks by referring to best practices in other countries.